JOINT VENTURE AGREEMENT AS A FORM OF INVESTMENT COOPERATION - Sri Purwaningsih; Agnes Maria Janni Widyawati (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2023)
According to the 1945 Constitution. The economic growth must promote equitable prosperity, high growth, and steady national stability. To achieve this goal, it is not easy, because the Indonesian people face many challenges. Ways that must be taken to extend financial development incorporate venture, utilize of innovation, increment information, move forward organizational and administration aptitudes. In this case, venture plays an imperative part. Joint Venture is a collaboration between foreign investors and foreign investors. In international business, joint ventures are used in various kinds of agreements, including joint production agreements (Corproduction Agreements), production sharing agreements (license agreements) and management contracts (Management Contracts).